Truth problematization and identity formation: a Foucauldian reading of Martin Amis's Money - Mohammed, Marwan Kadhim; Wan Yahya, Wan Roselezam; Jujar Singh, Hardev Kaur; Mani, Manimangai (Penerbit Universiti Kebangsaan Malaysia, 2016)
Transgression in postmodern age marked a unique social and cultural aspect in re-forming the identity of the postmodern man. Martin Amis mirrors the identities of his characters through their transgression of the social norms, specifically, the established norms of truth of masculinity. However, this idea of truth transgression in Amis's novel Money has not been fully taken into account and there has been little discussion about it in terms of identity formation. Thus, the aim of this paper is to investigate the way in which transgression of truth affects the idea of identity formation in Amis's novel Money. Drawing on Michel Foucault's technique of problematisation, the present paper investigates the notion of transgressing the historical truth of masculinity which becomes a significant idea that the protagonist John Self manipulates to actualise himself and to pick up his own identity. The paper reveals a conclusion in which transgression of truth can be instrumental in realising the self and re-affirming subjectivity as the case is in John Self.